Evaluation of the exposure time of a Bulk-Fill resin in deep preparations - Vásquez-Castro, Eva (2022)
Background: Bulk-fill composite  resins  (BF)  are  used  in  posterior  restorations  with  extensive  and  deep preparations. One of the most outstanding benefits is that it can be used in increments of 4 to 5 mm, reducing clinical working time. However, in teeth with root canal treatment, these preparations could be deeper. Objectives: To determine the photoactivation time necessary to polymerize a Bulk-Fill resin located in deep areas. Material and Methods: In the present experimental in vitro study, specimens of Filtek One Bulk Fill composite resin (3M ESPE, St. Paul, USA) of 5x5x5 mm color A2 photoactivated at a distance/time of 0 mm/10 s, 0 mm/20 s, 3 mm/10 s, 3 mm/20 s, 3 mm/30 s and 3 mm/40 s (n=5) were fabricated. Surface microhardness was recorded on the surface and at the base of each specimen. Results: The highest microhardness value was recorded in group BF 0 mm/20 s and BF 3 mm/40 s (p<0.05), followed by groups BF 3 mm/20 s and BF 3 mm/30 s (p>0.05). The lowest microhardness values were found in the BF 0 mm/10 s and BF 3 mm/10 s groups. Conclusion: It takes 40 s of photoactivation to polymerize a Bulk-Fill resin located in deep areas, when the lamp is 3 mm away from the resin surface.